Comparison of Angiographic Pattern & Complexity of Coronary Artery Disease between Diabetic and Non diabetic Women with Acute Coronary Syndrome (University Heart Journal, 2025)
Background: Coronary artery disease is responsible for more deaths in women each year than combined all other causes. Diabetes mellitus is a common metabolic disorder, that is a strong risk factor for the development of coronary artery disease in women regardless of age or menopausal status. But there are fewer studies describing the angiographic pattern and complexity of coronary artery disease in this group and whether diabetes mellitus is a key factor for this. Objective: The objective of this study is to find out the differences of angiographic patterns and complexity of coronary artery disease between diabetic and non-diabetic women presenting with acute coronary syndrome. Material and methods:.A total of 100 women (50 Diabetic and 50 non-Diabetic) who were diagnosed as a case of acute coronary syndrome and underwent coronary angiography were included in this study, following inclusion and exclusion criteria. Angiographic pattern was assessed by number of vessel involvement and complexity was determined by calculating the SYNTAX score. The pattern and complexity of coronary artery disease were compared between diabetic and non-diabetic women. Results: In this study, diabetic women had more triple vessel disease (42%), whereas Non-Diabetic women had more single vessel disease (50%). Left anterior decending artery (LAD) was the common artery involvement in both groups and involvement of individual coronary artery LCX, RCA was statistically significant (P values were 0.045 and 0.001 respectively). Complexity assessed by SYNTAX score showed Low SYNTAX score (≤22) was more in Non Diabetic women, High SYNTAX(>32) was more in Diabetic women and were statistically significant (p